FRIB cryogenic system status. Issue 1 (March 2020) - Casagrande, F; Ganni, V; Knudsen, P; Wright, M; Jones, S; Nguyen, C; Fila, A; Hassan, N; Vargas, G; Joseph, N; Stanley, S
Abstract: The Facility for Rare Isotope Beams (FRIB) cryogenic plant has been successfully commissioned, including compressor system, 4.5 K cold box system, sub-atmospheric (2 K) cold box system, and the distribution system for two of the three linear accelerator (Linacs) segments. This plant uses the Ganni-Floating pressure process, allowing the compressor discharge and 4.5 K cold box supply pressure to automatically vary from 6 to 21 bar, without introducing additional exergetic losses to reduce the capacity (e.g., throttling turbine inlet valves, load heaters, etc.). The 2 K (31 mbar) load is supported using five stages of centrifugal compressors, housed within the sub-atmospheric cold box, which recompress the helium to 1.15 bar (and around 30 K). In 2012, FRIB assumed the responsibility, in collaboration with JLab to design and procure the sub-systems after the decision to move away from an industry supplied turn-key system. FRIB was responsible for procurement of all systems, all onsite activities, including the installation and integration of all the subsystems, development of the control systems, as well as, the integration, commissioning, and testing of each sub-system. At present this has culminated in the production of the first beam through the first Linac segment. An overview of the planning and execution of the project will be presented, which allowed meeting of scheduled goals and anticipated performance, and prevented the need to store or 'double-handle' any equipment.